Compensation of Reactive Power of AC Catenary System. (2017) - Liudvinavičius, Lionginas
Abstract: The article analyses the theoretic and practical solutions of appearance of reactive power and compensation of it in the 25 kV, 50 Hz supply system of a contact network. The article proposes the theoretic (by using formulas, equivalent, structural schemes, phasor diagrams) and practical research (by providing the schemes of connecting capacitor banks, calculating the parameters of capacitor banks) for the compensation of reactive power. The main purpose of this article is to introduce and illustrate a new method of reactive power compensation.